1997
DOI: 10.1016/s0092-8674(00)80301-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Are Excitable Organelles Capable of Generating and Conveying Electrical and Calcium Signals

Abstract: We report Ca2(+)-induced release of Ca2+ from mitochondria (mCICR) dependent on transitory opening of the permeability transition pore (PTP) operating in a low conductance mode. The Ca2+ fluxes taking place during mCICR are a direct consequence of the mitochondrial depolarization spike (mDPS) caused by PTP opening. Both mDPS and mCICR can propagate from one mitochondrion to another in vitro, generating traveling depolarization and Ca2+ waves. Mitochondria thus appear to be excitable organelles capable of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
500
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(518 citation statements)
references
References 66 publications
(18 reference statements)
17
500
0
1
Order By: Relevance
“…A decrease of ⌬⌿ m can occur in a reversible manner without any cytochrome c release and cell death [47][48][49]. ATP depletion alone does not necessarily lead to depolarization of the mitochondria [34].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of ⌬⌿ m can occur in a reversible manner without any cytochrome c release and cell death [47][48][49]. ATP depletion alone does not necessarily lead to depolarization of the mitochondria [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short PTP opening is likely to mediate fast release of Ca 2 þ from mitochondria. 28,38,[40][41][42] As Ca 2 þ is the most important cellular permissive factor for PTP opening, the close coupling of mitochondrial and ER Ca 2 þ levels may provide an initial level of coordination between the action of the PTP and BCL-2 family members. A number of studies have demonstrated that members of the BCL-2 family reside not only in the OMM but also in the ER where they have opposing actions in regulating the transfer of ER Ca 2 þ to mitochondria; antiapoptotic members reduce ER Ca 2 þ and pro-apoptotic members promote Ca 2 þ mobilization from the ER to mitochondria during apoptosis, perhaps by regulating of the activity of the ER inositol trisphosphate receptor.…”
Section: An Integrated Modelmentioning
confidence: 99%
“…The PT pore participates in the regulation of matrix Ca 2+ , pH, DC m , and volume and functions as a Ca 2+ -, voltage-, pH-, and redox-gated channel with several levels of conductance and little if any ion selectivity (Bernardi and Petronilli, 1996;Ichas et al, 1997;Zoratti and SzaboÁ , 1995). PT pores are multiprotein complexes formed at the contact site between the mitochondrial inner and outer membranes, exactly at the same localization at which Bax, Bcl-2 and Bcl-X L are particularly abundant.…”
Section: Who Forms Channels In Vivo?mentioning
confidence: 99%
“…Unfortunately, the conclusion that cytochrome c is released early, before the DC m disruption occurs, is mostly based on experiments involving rhodamine 123, which is not always appropriate for DC m quantitation (Metivier et al, 1998). In any case, since the PT pore can function at di erent states of conductance and reversibility (Kinnally et al, 1996;Zoratti and SzaboÁ , 1995), it is possible that the function of the respiratory chain restores the DC m in conditions in which the PT is¯ickering (Ichas et al, 1997), although PT pore opening remains the primum movens for an increase in mitochondrial volume and cytochrome c release. In accord with this possibility, it has been found that a PT-mediated reversible loss of the DC m accompanied by cytochrome c release precedes glutamate-induced neuronal apoptosis (Ankarcrona et al, 1995).…”
Section: Molecular Composition Of the Pt Pore Complex ± Copuri®cationmentioning
confidence: 99%